THE EFFECTIVENESS OF INDEX CARD MATCH STRATEGY TO TEACH STUDENTS’ READING COMPREHENSION (A Pre- Experimental Research to the Eighth Grade Students of SMP Negeri 3 Sanggau in the Academic Year of 2018/2019) - Feri Jayanti; Aunurrahman Aunurrahman; Dian Shinta Sari (XXXX-XXXX, 2020)
The objective of this research were to find out whether there was any differences of students reading comprehension achievement before and after the implementation the treatment Index Card Match Strategy and how effective Index Card Match Strategy in reading comprehension to the Eight grade students of SMP Negeri 3 Sanggau in Academic Year of 2018/2019. The method of this research was quantitative research using experimental design. The result of the data showed the SD of pre-test (8.884) was higher than SD of post-test (7.863). It showed that the treatment was well implemented. Lastly it was proved by paired sample t-test value, the value of t-test was higher than t-table 19.165 2.064 which meant that Ha was accepted. The effect of the used Index Card Match Strategy was strong effect level based on the Cohen’s effect. It was 1.05 which meant that strong effect to increase students’ reading comprehension.  Keyword: Index Card Match Strategy, Reading Comprehension, Pre-Experimental Research